The Influence of AI and Price on Honda Motorcycle Purchasing Decisions at Astra - Safrida; Basri Modding; Andirwan; Fitrohdin Wahyu Sayekti; Martin (www.amertainstitute.com, 2024)
This research aims to find out whether Artificial Intelligence (AI) and price have a partially significant influence on the decision to purchase a Honda motorbike at Astra Motor Sidrap. Apart from that, this research also aims to identify the simultaneous influence of AI and price on purchasing decisions for Honda motorbikes at Astra Motor Sidrap. The method used in this research is a descriptive method with multiple linear regression data analysis techniques, which were analyzed using the SPSS 26 program. The data used is primary data obtained from the results of questionnaires filled out by respondents. The research results show that AI partially has a significant influence on the decision to purchase a Honda motorbike at Astra Motor Sidrap. Likewise, price partially has a significant influence on the decision to purchase a Honda motorbike at Astra Motor Sidrap. Meanwhile, simultaneously, AI and price have a significant influence on the decision to purchase a Honda motorbike at Astra Motor Sidrap.